Isocyanoalkene Addition–Cyclization–Decarboxylation Cascades - Marrazzo, John-Paul R.; Huynh, Tish; Fleming, Fraser F. (Synthesis, 2024)
A rare conjugate addition to isocyanoalkenes with ethyl cyanoacetate triggers an efficient addition–cyclization–decarboxylation cascade. Using finely dispersed NaOH in THF as a base and nucleophile, is critical in facilitating the proton transfers, the ester hydrolysis, and the subsequent decarboxylation. The strategy provides an efficient route to valuable nitrile-substituted 2,3-dihydro-1H-pyrroles while providing fundamental insight into conjugate additions to isocyanoalkenes.
Keywords: isocyanides; isocyanoalkenes; additions; cyclizations; cascades